This preview shows page 1. Sign up to view the full content.
Unformatted text preview: undetermined coecients. Thus, a particular solution to this nonhomogeneous equation will have the Form y p, 2 ( t ) = A 2 t 2 + A 1 t + A y p, 2 ( t ) = 2 A 2 t + A 1 y p, 2 ( t ) = 2 A 2 . Plugging these expressions into the equation y + y = t 2 + 1 yields y p, 2 + y p, 2 = 2 A 2 + A 2 t 2 + A 1 t + A = A 2 t 2 + A 1 t + (2 A 2 + A ) = t 2 + 1 . By equating coecients, we obtain A 2 = 1 , A 1 = 0 , 2 A 2 + A = 1 A = 3 . 220...
View
Full
Document
 Spring '10
 Hald,OH
 Math, Differential Equations, Linear Algebra, Algebra, Equations

Click to edit the document details